Dynamic Analysis of Impact Model of Slipping Tramcar Prevention Equipment Based on an Energy Absorber - Guiyun Xu; Shuo Hu; Xiaoguang Zhang; Jiazhou Zhu; Huipeng Zheng; Hongxin Wang (Shock and Vibration)
The protection equipment of slipping tramcar in inclined shaft is the important safety equipment to ensure safety production in mine transportation and equipment. The Slipping Tramcar Prevention Equipment is mainly composed of an intercepting door and a buffering system, in which an energy absorber is the key component. The braking dynamic model of the energy absorber is studied by establishing a Lagrange equation and simulating the braking progress by the software of Simulink. The braking simulation distances curves of the energy absorber are obtained under the different initial conditions of tramcar mass and velocity, which shows that the tramcar velocity and mass both have a significant influence on the braking distance. The analysis on variance and range is developed for further comparison on the two key factors implying that tramcar mass is of the most great importance. Moreover, a braking distance formula is built based on the analysis results. On the other hand, field experiments are conducted in Qishan Mine, and experiment results show that the maximum error between the braking distance formula value and the experiment value is 11.98%, and the minimum error is 2.72%. The experimental results are consistent with the theoretical results.